2021
DOI: 10.1007/s10886-021-01263-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Behavioral Responses of an Ambrosia Beetle to Volatiles of its Nutritional Fungal Symbiont

Abstract: Ambrosia beetles (Coleoptera: Scolytinae) cultivate their fungal symbiont within host substrates as the sole source of nutrition on which the larvae and adults must feed. To investigate a possible role for semiochemicals in this interaction, we characterized electrophysiological and behavioral responses of Xylosandrus germanus to volatiles associated with its fungal symbiont Ambrosiella grosmanniae. During still-air walking bioassays, X. germanus exhibited an arrestment response to volatiles of A. grosmanniae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
(109 reference statements)
1
12
1
Order By: Relevance
“…Compound βcaryophyllene, previously described as a potential biofumigant, was also dominantly emitted by the ambrosia fungus F. solani (Egonyu and Torto, 2018). In particular, ambrosia beetles exhibited a strong attraction to ethanol, which is also emitted by susceptible host trees (Ranger et al, 2021) and has been reported to promote the growth of fungal symbionts Ambrosiella spp. while reducing that of other competing fungi (Ranger et al, 2018).…”
Section: Fungi With Antifungal Activity Against Ambrosia Fungimentioning
confidence: 96%
See 3 more Smart Citations
“…Compound βcaryophyllene, previously described as a potential biofumigant, was also dominantly emitted by the ambrosia fungus F. solani (Egonyu and Torto, 2018). In particular, ambrosia beetles exhibited a strong attraction to ethanol, which is also emitted by susceptible host trees (Ranger et al, 2021) and has been reported to promote the growth of fungal symbionts Ambrosiella spp. while reducing that of other competing fungi (Ranger et al, 2018).…”
Section: Fungi With Antifungal Activity Against Ambrosia Fungimentioning
confidence: 96%
“…Interestingly, the use of fungal VOCs has also been explored as lures for ambrosia beetles Egonyu and Torto, 2018;Ranger et al, 2021), as beetles showed to be particularly attracted to VOCs emitted by their fungal symbionts. Alcohols such as ethanol, 2-methyl-1-propanol and 3-methyl-1-butanol were detected in the volatile profiles of Ambrosiella sp., R. lauricola, and F. solani associated with Xylosandrus compactus (Kuhns et al, 2014;Egonyu and Torto, 2018).…”
Section: Fungi With Antifungal Activity Against Ambrosia Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…For example, fungi that release higher amounts of 3-methyl-1-butyl acetate, 2-methyl-1-butyl acetate and 2-phenetyl acetate are highly attractive ( Kandasamy et al, 2019 , 2023 ) . Other studies have shown that several species of ambrosia beetles in the Xylosandrus , Xyleborus , and Xyleborinus genera are attracted to their fungal symbiont odors and the response may be modulated by the addition of compounds such as ethanol ( Hulcr et al, 2011 ; Egonyu and Torto, 2018 ; Ranger et al, 2021 ). In addition, recent electrophysiological studies of the OSNs in I. typographus revealed several abundant OSN classes specifically tuned to odors derived from I. typographus fungal symbionts ( Kandasamy et al, 2019 , 2023 ).…”
Section: Introductionmentioning
confidence: 99%